Demonstration of the XWand Interface for Intelligent Spaces - Wilson, Andy (UIST '02 - Adjunct Proceedings of the 15th annual ACM Symposium on User Interface Software and Technology, 2002)
The XWand is a novel wireless sensor package that enables styles of natural interaction with intelligent environments. For example, a user may point the wand at a device and control it using simple gestures. The XWand system leverages the intelligence of the environment to best determine the user’s intention. We demonstrate the wand hardware device and multimodal (wand and speech) interpretation process in variety of device control scenarios, including lighting, media player, and cursor control.